Dynamics of Green and Blue Water Supply Stress Index Across Major Global Cropland Basins - Khand, Kul; Senay, Gabriel B.; Kagone, Stefanie; Parrish, Gabriel Edwin Lee (Frontiers in Climate, 2021)
Global food and water security could be serious problems in the upcoming decades with growing demands from the increasing global population and more frequent impacts of climatic extremes. As the available water resources are diminishing and facing continuous stress, it is crucial to monitor water demand and water availability to understand the associated water stresses. This study assessed the water stress by applying the water supply stress index (WaSSI) in relation to green (WaSSIG) and blue (WaSSIB) water resources across six major cropland basins including Mississippi (North America), San Francisco (South America), Nile (Africa), Danube (Europe), Ganges-Brahmaputra (Asia), and Murray-Darling (Australia) for the past 17-years (2003-2019). The WaSSIG and WaSSIB results indicated that the Murray-Darling Basin experienced the most severe green and blue water stresses and the Mississippi Basin had the least. All basins had both green and blue water stresses for at least 35% (6 out of 17 years) of the study period. The interannual variations in green water stress were driven by both crop water demand and green water supply, whereas the blue water stress variations were primarily driven by blue water supply. The WaSSIG and WaSSIB indices provided a better understanding of water stress (blue or green) and their drivers (demand or supply driven) across cropland basins. This information can be useful for basin-specific resource mobilization and interventions to ensure food and water security.